Selection of Candidates for Positions in Higher Education Institution from the Standpoint of Their Potential Loyalty to Employer - A. R. Alaverdov; T. P. Alaverdova (Высшее образование в России)
The article focuses on the personal characteristics of candidates for employment in higher education institutions. The presence of a number of features in a candidate, with high probability, determines their potential disloyalty to any employer in the system of higher education. The authors explore the personal qualities, psychological types, habits and inclinations of lecturers, as well as other employees of University, which can provoke various threats to its reputation, information and property security. The article makes the case for using special HR-technologies as a necessary element of the recruitment procedure in modern University. HR-technologies such as stress interview questions, 16PF Questionnaire, Questionnaire of K. Leonhard - S. Shmishek, Eysenck Personality Questionnaire, State-Trait Anxiety Inventory, Buss-Durkey Inventory and others make it possible to identify the above negative qualities and, thus, to prevent most of possible threats to the personnel security of higher education institution. The article formulates the practice-oriented recommendations on the solution ofthe considered problem.